The cluster-based development strategy in Kazakhstan's agro-food sector: A critical assessment from an Austrian perspective; Die Clusterförderungsstrategie im Agrar- und Ernährungssektor Kasachstans: Eine kritische Bewertung aus Sicht der Österreichischen Schule - Jürgen Wandel (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
This paper challenges the uselfullness of the cluster-based development strategy to diversify and increase the competitiveness of Kazakhstan's economy, regarding the case of the country's agro-food sector. For this it refers to insights of the Austrian Market Process Theory. It is argued that already the theoretical foundations of the cluster concept suffer from severe difficiencies, because it widely neglects the function of competition as a discovery procedure with alert entrepreuneurs as the driving force. Moreover, it ignores the knowledge requirements and limitations in a modern market economy for any outside third party to identify and promote successful industry structures. The closer examination of the implementation of the cluster development program in Kazakhstan's agro-food sectors shows that cluster facilitation in practice turned out to be another form of social engineering and picking winners. In the light of the Austrian understanding of the market system as an entrepreneurial discovery process the paper suggestes as alternative policy option to concentrate on the establishment of a stable institutional framework for the whole economy that stimulates the entrepreneurial discoveries of profitable businesses. Yet, such an Austrian approach is politically less appealing, for it might bring no quick results due to the prevalence of conflicting informal institutions which in the short run might be difficult to change. – – Der Beitrag diskutiert die Eignung der Clusterförderungspolitik zur Diversifizierung und Verbesserung der Wettbewerbsfähigkeit der Volkswirtschaft Kasachstans am Beispiel der Agrar- und Ernährungswirtschaft des Landes. Dazu wird auf Erkenntnisse der Marktprozeßtheorie der Österreichischen Schule zurückgegriffen. Es wird argumentiert, daß allein schon die theoretische Fundierung der Clusterförderungspolitik fraglich ist, weil sie die Funktion des Wettbewerbs als eines Entdeckungsverfahrens mit findigen Unternehmern als treibende Kraft vernachlässigt. Darüber hinaus unterschätzt sie die Anforderungen an das Wissen, das staatliche Akteure und beratende Ökonomen haben müßten, um erfolgversprechende Industrie- und Unternehmensstrukturen identifizieren und fördern zu können. Die Analyse der Umsetzung der Clusterförderungspolitik in Kasachstans Agrar-und Ernährungswirtschaft zeigt, daß sie praktisch nichts anderes ist als eine weitere Form von staatlichem Konstruktivismus und einer Politik der picking winners. Ausgehend vom Verständnis der Österreichischen Schule des Marktsystems als eines von findigen Unternehmern getragenen Entdeckungsverfahrens schlägt der Beitrag als alternative Strategie vor, sich auf den Aufbau von verlässlichen institutionellen Rahmenbedingungen zu konzentrieren, die für alle Sektoren der kasachstanischen Volkswirtschaft gleichermaßen gelten und die geeignet sind, den unternehmerischen Entdeckungsprozeß zu fördern. Aus politischen Gründen dürfte jedoch diese österreichische Politikoption wenig attraktiv sein, da sie langfristig angelegt ist und kurzfristig nicht zuletzt aufgrund des Konflikts zwischen formalen und informalen Institutionen keine sichtbaren Resultate erwarten lässt.
urn:nbn:de:gbv:3:2-10641
Keywords: B53; Q13; L22; L52; 330; Cluster; Kazakhstan; industrial policy; institutional change; Cluster; Kasachstan; Industriepolitik; institutioneller Wandel